Penggunaan Kata Tabu dalam Tuturan Pembaca Berita “Pojok Kampung” JTV - Andriani, Viena Wanidha (INCARE, International Journal of Educational Resources, 2024)
This research aims to describe the types and examples of taboo words used by news readers on JTV's "Pojok Kampung" program, East Java, which are distinctive or unique and different from news programs in general. This research is descriptive qualitative research. The data source in this research is the speech of the JTV "Pojok Kampung" news presenters. The data collection technique used is listening and note-taking technique. Wardhaugh's theory is applied in this research to identify the types of taboo words used in the news broadcast "Pojok Kampung". From the results of the analysis, it was found that in the program "Pojok Kampung" which was broadcast on JTV station, there were taboo words used by news readers, namely taboo words related to sex, the natural functions of the human body, and taboo words related to death.